Dehydration of d-fructose to 5-hydroxymethyl-2-furfural in DMSO using a hydrophilic sulfonated silica catalyst in a process promoted by microwave irradiation - Barbosa, Sandro L.; de S. Freitas, Milton; dos Santos, Wallans T. P.; Nelson, David Lee; Klein, Stanlei I. [UNESP]; Clososki, Giuliano Cesar; Caires, Franco J.; Baroni, Adriano C. M.; Wentz, Alexandre P. (Springer Nature, 2021)
SiO2-SO3H, with a surface area of 115 m2/g, pore volumes of 0.38 cm3g−1 and 1.32 mmol H+/g, was used as a 10% w/w catalyst for the preparation of 5-hydroxymethyl-2-furfural (HMF) from fructose. A conversion of 100% was achieved in a microwave reactor during 10 min at 150 °C in DMSO, with 100% selectivity for HMF, at a molar ratio of fructose: DMSO equal to 1:56. The catalyst could be re-used three times.